Single-cell sequencing reveals PHLDA1-positive smooth muscle cells promote local invasion in head and neck squamous cell carcinoma - Bing Guo; Xutao Wen; Shun Yu; Jun Yang (Translational Oncology)
Background: Smooth muscle cells within the tumor microenvironment play a crucial role in cancer progression. However, their involvement in the local invasion of head and neck squamous cell carcinoma remains poorly understood. In this research, we aim to investigate the role of smooth muscle cells-mediated cell interactions in facilitating the local invasion of head and neck squamous cell carcinoma. Methods: Single-cell sequencing data from the public databases GSE164690 and GSE181919 were utilized to identify a specific smooth muscle cells cluster. Smooth muscle cells were isolated from tumor microenvironment of head and neck squamous cell carcinoma. PHLDA1 expression in smooth muscle cells was assessed through immunofluorescence staining. The role of THBS1 was investigated through in vitro studies. Results: PHLDA1-positive smooth muscle cells were significantly enriched in head and neck squamous cell carcinoma. PHLDA1 promoted the expression of THBS1 in smooth muscle cells. In vitro, THBS1 facilitated head and neck squamous cell carcinoma migration and invasion through SDC1 receptor. Conclusion: PHLDA1-positive smooth muscle cells play a critical role in head and neck squamous cell carcinoma invasion through THBS1. Targeting PHLDA1-positive smooth muscle cells or THBS1 may offer a promising therapeutic approach for head and neck squamous cell carcinoma treatment.